2013
DOI: 10.1186/1479-5868-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental feeding practices in Mexican American families: initial test of an expanded measure

Abstract: BackgroundAlthough obesity rates are high among Latino children, relatively few studies of parental feeding practices have examined Latino families as a separate group. Culturally-based approaches to measurement development can begin to identify parental feeding practices in specific cultural groups. This study used qualitative and quantitative methods to develop and test the Parental Feeding Practices (PFP) Questionnaire for use with Mexican American parents. Items reflected both parent’s use of control over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
4
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 49 publications
5
97
4
12
Order By: Relevance
“…Further qualitative research into different racial/ethnic groups' conceptualizations of controlling feeding practices (e.g., Rodríguez-Oliveros et al, 2011) and further modification of existing self-report measures or development of culturally sensitive questionnaires (e.g., Tschann et al, 2013) may be necessary to account for racial/ethnic differences.…”
Section: Tablementioning
confidence: 99%
“…Further qualitative research into different racial/ethnic groups' conceptualizations of controlling feeding practices (e.g., Rodríguez-Oliveros et al, 2011) and further modification of existing self-report measures or development of culturally sensitive questionnaires (e.g., Tschann et al, 2013) may be necessary to account for racial/ethnic differences.…”
Section: Tablementioning
confidence: 99%
“…4 In terms of nutrition intake, parental feeding behavior plays an important role in creating children's eating experiences and how it would link to children's eating behavior and nutritional status. [5][6][7][8][9][10] Inappropriate parents' feeding behaviors will lead not only to underweight but also to overweight problems. [6][7][8]10 Additionally, children whose parents have poor feeding practice are likely more prone to some health problems.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Inappropriate parents' feeding behaviors will lead not only to underweight but also to overweight problems. [6][7][8]10 Additionally, children whose parents have poor feeding practice are likely more prone to some health problems. [11][12][13] Parental feeding behaviors, which are the activities of parents in maintaining adequate food intake for their toddlers, involve more than just feeding activities.…”
Section: Introductionmentioning
confidence: 99%
“…This allows their children to make healthy food choices and reinforce their good eating habits. Children who follow their inner signals learn to eat properly according to their feelings of their hunger or fullness and can be said to have developed nutritional self-efficacy [17,18]. Studies of the relationship between obesity and self-efficacy have shown that people with higher levels of self-efficacy consume healthier foods [19,20], indicating a negative correlation between obesity and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%